2021
DOI: 10.1146/annurev-earth-071420-053134
|View full text |Cite
|
Sign up to set email alerts
|

The Organic Isotopologue Frontier

Abstract: Organic molecules are key components of the Earth-life system. Their stable isotope composition provides information on various problems such as past climate, energy resources, or the synthesis of prebiotically relevant molecules on Earth and elsewhere. Organic molecules are made of isotopologues, molecules differing in the number and/or position of isotope substitution. Recent years have witnessed a boom in technological development dedicated to isotopologue measurement, leading to an unprecedented degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 141 publications
0
33
0
Order By: Relevance
“…Previous studies have also demonstrated that differences in the bulk and position-specific 13 C isotope composition of propane can be influenced by the source, the rate and temperature of gas formation as well as secondary processes such as migration or diffusion [21,35,36]. A different original source of hydrocarbons is supported by the higher 13 C/ 12 C ratios for methane and ethane in Gamou compared with those in Murono (Table 2).…”
Section: Position-specific 13 C Composition Of Propanementioning
confidence: 77%
See 2 more Smart Citations
“…Previous studies have also demonstrated that differences in the bulk and position-specific 13 C isotope composition of propane can be influenced by the source, the rate and temperature of gas formation as well as secondary processes such as migration or diffusion [21,35,36]. A different original source of hydrocarbons is supported by the higher 13 C/ 12 C ratios for methane and ethane in Gamou compared with those in Murono (Table 2).…”
Section: Position-specific 13 C Composition Of Propanementioning
confidence: 77%
“…The past few years have witnessed a boom in hydrocarbon isotopic analysis with the advent of isotopologue analysis. Isotopologues are molecules that differ in the number and/or position of isotope substitution [ 11 , 12 ]. These include multiply substituted isotope species such as 13 C H 3 D and CH 2 D 2 for methane [ 13 , 14 , 15 , 16 ], 13 C H 3 - 13 C H 3 for ethane [ 17 , 18 ], as well as position-specific isotopologues such as 13 C H 3 -CH 2 -CH 3 and CH 3 - 13 C H 2 CH 3 of propane [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acid PSIA has been achieved previously by a range of methodologies, including isotopic nuclear magnetic resonance (NMR) spectroscopy of intact molecules, and IRMS coupled to online or offline chemical and/or thermal degradation (for reviews, see Refs [20][21][22] ). Most prior amino acid PSIA studies have targeted pre-purified analytes, purchased commerciallyreflecting the challenges of isolating amino acids from natural samples in large enough quantities or with sufficient purity for existing measurement strategies.…”
Section: Intramolecular Carbon Isotope Fractionations Have Been Observedmentioning
confidence: 99%
“…Both approaches involve laboratory-based instrumentation, and the samples are unavoidably destroyed either before (e.g., pyrolisis) or during analysis. Nevertheless, they were successfully applied to measure the intramolecular 13 C distribution of natural gas samples of thermogenic origin. These pioneering studies revealed that thermogenic propane exhibits systematic variations in the carbon isotope structure. However, more detailed research and widespread applications are required to better understand the various processes and pathways that occur in natural gas systems.…”
Section: Introductionmentioning
confidence: 99%